TEACHER PEDGOGIC COMPETENCE IN SOCIAL EMOTIONAL DEVELOPMENT IN EARLY CHILDREN 5-6 YEARS - Nurhasanah Nurhasanah; Zukhairina Zukhairina; Syahran Jailani (STAH Dharma Sentana Sulawesi Tengah, 2023)
The purpose of this study was to analyze the pedagogic competence of teachers in the socio-emotional development of children aged 5-6 years and what causes the pedagogic competence of teachers to be not optimal in the socio-emotional development of children aged 5-6 years and the efforts that teachers can make in optimizing the pedagogic competence of teachers in developing emotional social of children aged 5-6 years. The research method uses descriptive qualitative methods. Data was collected by observation, interviews and documentation. Data analysis used the Miles and Huberman model, namely data reduction, data presentation, data verification and confidence testing using data triangulation. The results of this study are the pedagogic competence of teachers in the social emotional development of children aged 5-6 years can be said to be optimal with the help of teachers and the assistance of facilities and infrastructure as well as their cohesiveness in carrying out cooperation in making lesson plans. Although there are inhibiting factors in implementing good pedagogic competencies, namely the educational status of teachers, factors from infrastructure and school administration factors.